(untitled) (Scripta : English Department Journal, 2023)
The purpose of this research is to determine adult in using chatbot for writing skill at home. this research approach was descriptive quantitative method. It aims to providea description of the difficulties of adults in improving writing skills in Muhammadiyah University of Jakarta. In collecting data, The instrument utilized by the researcher was a questionnaire. A questionnaire was conducted to determine the percentage of adults who were influenced by chatbots to improve their writing skills. Each question has five (5) answer categories to choose from. The questionnaire consists of several statements related to implementation of chatbot media to improve writing skills. For the first statement It was 90% of students agreed that writing is important. For the second statement There were 81% of pupils who said they enjoyed their writing skills. For the third statement is 71% of respondents said they like it. For the forth statement is 67% of people said that writing is tough. For the fifth statement there were 62% like replies. For the sixth statement there were 67% helpful responses. For the seventh statement there were 62% like answers. For the eighth statement is the pupils gave easy said in 81% of the responses. For the nineth statement The students provided 62% helpful responses. For the tenth statement there were 67% interested responses from the students. The researcher concluded that almost all of the students agreed if their teacher used chatbot media in the process of teaching English.